Impact of dry needling and ischemic pressure in the myofascial syndrome: controlled clinical trial - Rebeka Borba da Costa Santos; Maíra Izzadora Souza Carneiro; Déborah Marques de Oliveira; Adriana Baltar do Rêgo Maciel; Kátia Karina do Monte-Silva; Maria das Graças Rodrigues Araújo
Introduction Musculoskeletal pain is a common clinical condition and about 10% of the population have musculoskeletal disorder. Objective The aim of this study was to evaluate whether ischemic pressure and dry needling techniques are able to reduce the pain of patients with myofascial pain syndrome. Method 22 patients aged 20-75 years were randomized into 3 groups: ischemic pressure (IPG = 8), dry needling (DNG = 7) and control (CG = 7). Patients in the IPG and DNG were assessed before and after 10 intervention sessions, which occurred 3 times per week. The CG was assessed initially and reassessed three weeks later. The assessment of pain was done through Visual Analogic Scale (VAS) and quality of life through WHOQOL-BREF (5 domains: global, physical, psychological, social and environmental). Results There was no significant difference for clinical and demographic data of all groups at baseline, except for age (p = 0.042). The results of the VAS expressed that IPG had pain relief in most sessions, the same was not observed for DNG. Comparing the 2 groups was obtained difference in the 4th and 8th sessions. The results of the WHOQOL-BREF showed that the three groups had a significant increase in the psychological domain. The same was not true for global domains, physical, environmental and social. Conclusion Ischemic pressure and dry needling were able to reduce the pain of patients and also change their quality of life, specifically the psychological aspect.